2020
DOI: 10.1515/pteridines-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Folate-targeted PTEN/AKT/P53 signaling pathway promotes apoptosis in breast cancer cells

Abstract: Objective Folate deficiency is closely related to the occurrence of human tumors and plays an important role in cell growth, differentiation, repair, and host defense. We studied the effects of folic acid on the apoptosis of breast cancer cells (MDA-MB-231) and on the activity of the PTEN/AKT/P53 signaling pathway in breast cancer cells.Methods Breast cancer cells (MDA-MB-231) were treated with folate alone or in combination with a PTEN specific inhibitor, SF1670. Cell viability was detected by a MTT assay, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Additionally, a majority of clinical and randomized clinical trials have shown that methyl-donor micronutrient intake affects DNA methylation by reducing the risk of several cancer types [ 3 ]. Furthermore, folate can induce apoptosis via the PTEN/AKT/P53 signaling pathway, and through reducing the effects of both the AKT and ERK signaling in breast cancer [ 18 , 19 ]. It is known that AKT signaling can inhibit the activation of the pro-apoptotic Caspase-9 and Caspase-3 [ 20 ], and that upstream inhibitors of the MAPK pathway can reduce tumor proliferation and mediate apoptosis, though Erk1/2 activation may also be involved in apoptosis induction [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a majority of clinical and randomized clinical trials have shown that methyl-donor micronutrient intake affects DNA methylation by reducing the risk of several cancer types [ 3 ]. Furthermore, folate can induce apoptosis via the PTEN/AKT/P53 signaling pathway, and through reducing the effects of both the AKT and ERK signaling in breast cancer [ 18 , 19 ]. It is known that AKT signaling can inhibit the activation of the pro-apoptotic Caspase-9 and Caspase-3 [ 20 ], and that upstream inhibitors of the MAPK pathway can reduce tumor proliferation and mediate apoptosis, though Erk1/2 activation may also be involved in apoptosis induction [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…102 The developed platform is composed of dual-loaded niosomes with letrozole (Let) and cyclophosphamide (Cyclo) (NLC), and folic acid (FA) functionalized on the surface (NLCPFA) and can activate apoptosis, reduce Bcl-2 expression, and increase Bax expression by targeting the PTEN/AKT/P53 signaling pathway. 107 Niosome NPs contain an equal amount of both drugs, and formulation optimization features have been investigated using various surfactant-cholesterol molar proportions of 1 : 1 and 2 : 1 and lipid-drug molar proportions of 10 : 1 and 20 : 1, that affected the EE. 108 EE values of samples improved by 2–3% for each drug at the greater surfactant:cholesterol and lipid:drug molar proportions.…”
Section: Dual Niosomes For Cancer Therapymentioning
confidence: 99%